IT Service Quality as A Moderator Between Digital Attendance Application Usage and Employee Performance: Evidence from Indonesian Local Government - Nur Aziiza Syam; Asriani; Andi Zulkifli Nusri; Andi Adawiah; Muhammad Iqbal (Academic Bright Collaboration, 2026)
Purpose - This study aims to analyze the direct influence of digital attendance application (APATOKI) usage and IT service quality on employee performance, as well as to investigate the moderating role of IT service quality in the relationship between application usage and performance within a local government setting. Methods - A quantitative approach with a multivariate regression design was employed. Data were collected from 400 State Civil Apparatus (ASN) personnel in Soppeng Regency, South Sulawesi, who actively used the APATOKI application, selected through purposive sampling based on specific criteria. The instrument utilized a 5-point Likert scale to measure three variables: APATOKI usage, IT service quality, and employee performance. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Findings -The results demonstrate that both APATOKI usage (β = 0.254, p < 0.05) and IT service quality (β = 0.249, p < 0.05) have a significant positive direct effect on employee performance. More importantly, IT service quality was found to significantly moderate the relationship between APATOKI usage and performance (β = 0.187, p < 0.05). The model explained 69.9% of the variance in employee performance (R² = 0.699). Implications – This study shows that digital performance gains in public sector systems are contingent on the interaction between technology usage and IT service quality, shifting the focus from isolated technology adoption toward integrated system–service ecosystems as drivers of employee performance. Originality – This study provides a novel contribution by empirically demonstrating the moderating role of IT service quality in strengthening the impact of digital application usage on performance, integrating TAM, IS Success Model, and SERVQUAL into a single tested framework within a local government context.